Study of the Incorporation of Nano-SiO2 in High-Performance Concrete (HPC) - Alvansaz, Mohammad Farid (2022)
This research project aims to study the influence of the addition of nanosílice particles on the physical and mechanical properties of high-performance concrete: compression resistance, tensile strength, elastic module, Poisson module and break module. Nanosilica particles were included as a replacement of 0.75%, 1.5% and 3% by weight of the cement amount of a pattern concrete and also replacements of 5% and 10% of microsilica. The high performance concrete was designed to fulfill the characteristics of having a f’c greater than 55 MPa and having high workability, to meet the desired workability, a superplastifying additive was used. Microscopy test were conducted to determine the influence of silica additions in the microstructure and in the hydration of the concrete. From the results obtained, it was concluded that the optimal percentage of nanosilica is 1.5%. At 28 days of age, the results of the tests carried out determined that the optimal percentage of nanosilica with respect to the pattern concrete and the microsilica concretes produces an improvement of: resistance to compression of 8.44% and of 7.52%, tensile strength of 4.31% of 26.30%, break module of 16.21% of 9.63%, and elasticity module of 16.53% and 4.51% respectively. Nanosilica replacement showed to be viable and beneficial for the physical-mechanical properties of high performance concrete.